A research on employment and unemployment: Case in Turkey - Aşçı, Mehmet Saim; Öz, Sabri (My University, 2019)
Purpose – It is to evaluate active employment policies by examining the types of unemployment inTurkey.Design/methodology/approach – The methodology of this article is literature review. For Turkey’semploymen policy, the type of unemploıyment, Dynamics of unemploymen and the characteristicsof unemployment subjects are investigated. After a brief introduction, the coming first part of thearticle consists of general concepts of employment and unemployment. In the second part majörunemployment types have been investigated. Next part is about the employment policy and thedynamic factors of employment. At the end of the article it has been discussed whether active andpassive employment policies are enough or not for Turkey.Findings – The articles main outcomes are the basic conceptual information about employmentand unemployment where as the main findings are the edequacy of the current applied policyespecially on active employment policy in Turkey. It is important that under technologicaldevelopment the traditional policies should be transformed.Discussion – The main discussion subject is the policies which are used for decreasingunemployment are enough or not as education and technology Fundamentals are intransformation.
Keywords: Employment Policy; Unemploiyment; Active Employment Policy